Studies on the interactions between bile salts and food emulsifiers under in vitro duodenal digestion conditions to evaluate their bile salt binding potential - Naso, Julieta Natalia (2019)
During the last decade a special interest has been focused on studying the relationship between the composition and structure of emulsions and the extent of lipolysis, driven by the necessity of modulate lipid digestion to decrease or delay fats absorption or increase healthy fat nutrients bioavailability. Because bile salts (BS) play a crucial role in lipids metabolism, understanding how typical food emulsifiers affect the structures of BS under duodenal conditions, can aid to further understand how to control lipids digestion. In the present work the BS-binding capacity of three emulsifiers (Lecithin, Tween 80 and β-lactoglobulin) was studied under duodenal conditions. The combination of several techniques (DLS, TEM, ζ-potential and conductivity) allowed the characterization of molecular assemblies resulting from the interactions, as modulated by the relative amounts of BS and emulsifiers in solution.